Implementasi Akuntansi Kombinasi Bisnis dan Analisis Kinerja Keuangan Sebelum dan Setelah Penerapan PSAK 22 Pada PT GoTo Gojek Tokopedia Tbk (International Forum of Researchers and Lecturers, 2024)
This research explains the implementation of business combination accounting at PT GoTo Gojek Tokopedia Tbk after implementing PSAK 22, describing its impact on the company's financial performance. Through analysis of ROA, ROE and profit margin, the results show performance fluctuations after the Gojek and Tokopedia merger. Despite an increase in profit margin in 2022, ROA and ROE have decreased, bringing attention to the challenges facing the company. This research encourages companies to evaluate strategies to improve operational efficiency and maintain investor confidence. Limitations of the study involve its focus on one company and a specific time period. Recommendations for future research include involving more companies, considering specific factors that influence performance, and exploring the psychological impact of investors. The research findings provide practical and academic insight into business combination accounting and its implications for company financial performance in the era of globalization and industrial transformation.